The DIF1 gene of Arabidopsis is required for meiotic chromosome segregation and belongs to the REC8/RAD21 cohesin gene family. - Bhatt, A; Lister, C; Page, T; Fransz, P; Findlay, K; Jones, G; Dickinson, H; Dean, C (1999)
Cohesins are a group of conserved proteins responsible for cohesion between replicated sister chromatids during mitosis and meiosis and which are implicated in double-strand break repair and meiotic recombination. We describe here the identification and characterisation of an Arabidopsis gene - DETERMINATE, INFERTILE1 (DIF1), which is a homolog of the Schizosaccharomyces pombe REC8/RAD21 cohesin genes, and is essential for meiotic chromosome segregation. Five independent alleles of the DIF1 gene were isolated by transposon mutagenesis, and the mutants show complete male and female sterility. Pollen mother cells (PMCs) of dif1 mutants show multiple meiotic defects which are represented by univalent chromosomes and chromosome fragmentation at metaphase I, and acentric fragments and chromatin bridges in meiosis I and II. Consequently, chromosome segregation is strongly affected, resulting in meiotic products of uneven size, shape and of variable ploidy. The similarities in phenotype, and the sequence homology between DIF1 and the REC8/RAD21 cohesins suggests that cohesin function is largely conserved between eukaryotes and highlights the essential role cohesins play in plant meiosis.